PEMANAS INDUKSI UNTUK BALL BEARING DIAMETER NOMINAL 15,17, DAN 20 MM - Febriyan Azril Mohamad; Dista Yoel Tadeus; Fakhruddin Mangkusasmito; Ari Bawono Putranto (BERKALA FISIKA, 2023)
Bearing is an important component in supporting engine performance. However, according to a study by Svenska Kullager Fabriken (SKF), bearings are also one of the components that most often cause 40% of engine damage. Bearing damage occurs during installation which is still done manually, namely being hit which results in high friction on the wheel axles. To overcome this, a tool is made with the heating method to carry out bearing installation which utilizes expansion of the bearing. Induction heating device, is a solution for heating bearings which has not been produced in Indonesia. Therefore, an induction heating system was created for heating bearings using the NodeMCU ESP8266 microcontroller as a controller and using a type k thermocouple temperature sensor as a temperature detector with the PID method. The use of this PID method as a heating temperature control when it reaches the desired set point, the heating process will automatically stop. The objects used are bearings with inner rings of 15mm, 17mm and 20mm. By making this induction heater, the performance of the tool is obtained with an average heating time to reach a set point temperature of 100OC is 3.64 minutes.